Investigation of thermal degradation of poultry processing dewatered sludge using thermogravimetric analysis method - Aniza, N. (Penerbit UTM Press, 2015)
Thermal degradation of Poultry Processing Dewatered Sludge (PPDS) was studied using thermogravimetric analysis (TGA) method. The effect of particle size on PPDS samples and operational condition such as heating rates were investigated. The non-isothermal TGA was run under a constant flow of oxygen at a rate of 30 mL/min with temperature ranging from 30ºC to 800ºC. Four sample particle sizes ranging between 0.425 mm to 2 mm, and heating rate between 5 K/min to 20 K/min were used in this study. The TGA results showed that particle size does not have any significant effect on the thermogravimetry (TG) curves at the initial stage, but the TG curves started to separate explicitly at the second stage. Particle size may affect the reactivity of sample and combustion performance due to the heat transfer and temperature gradient. The TG and peak of derivative thermogravimetry (DTG) curves tend to alter at high temperature when heating rate is increased most likely due to the limitation of mass transfer and the delay of degradation process. © 2015 Penerbit UTM Press. All rights reserved.